2021
DOI: 10.7759/cureus.19554
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Antenatal Care Utilization Among Pregnant Women in Qassim, Saudi Arabia

Abstract: Background and objectives Coronavirus disease 2019 (COVID-19) pandemic has affected routine service delivery which might affect antenatal care (ANC) utilization among pregnant women. This study aimed to assess the proportion of missed appointments among pregnant women in the Qassim region of Saudi Arabia during the COVID-19 pandemic. Methods A facility-based cross-sectional survey was conducted among pregnant women admitted for delivery in Maternity and Children Hospital (MCH),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
1
14
0
2
Order By: Relevance
“…However, another study conducted during the pandemic in Saudi Arabia has contradictory findings as the adherence of pregnant women to ANC visits during the pandemic was much lower than that of general data before the pandemic. Specifically, this study has found that 30.0% of mothers involved missed or delayed their ANC appointment during the COVID-19 pandemic period [19]. This finding can be attributed to that this study has been performed relatively early in the time (end of 2020) of the pandemic era.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…However, another study conducted during the pandemic in Saudi Arabia has contradictory findings as the adherence of pregnant women to ANC visits during the pandemic was much lower than that of general data before the pandemic. Specifically, this study has found that 30.0% of mothers involved missed or delayed their ANC appointment during the COVID-19 pandemic period [19]. This finding can be attributed to that this study has been performed relatively early in the time (end of 2020) of the pandemic era.…”
Section: Discussionmentioning
confidence: 77%
“…In Saudi Arabia, the government applied prompt preventive measures against coronavirus disease 19 (COVID- 19). Saudi Arabia implemented policies of availability of personal protective equipment, stay-at-home, social distancing, and quality hospital care to the people [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Antenatal care Utilization Among Pregnant Women in Qassim, Saudi Arabia. (Rabbani et al, 2021) Sekitar sepertiga (30%) wanita telah melewatkan setidaknya satu janji ANC dalam kehamilan mereka saat ini. Alasan paling umum untuk melewatkan janji ANC di fasilitas kesehatan primer dan rumah sakit, masing-masing, adalah: ketakutan akan infeksi 52% dan 47%, fasilitas tidak berfungsi seperti biasa 25% dan 7,5%, takut tertular pada anak 19% dan 17%.…”
Section: Impact Of Covid-19 Onunclassified
“…Selanjutnya, wanita hamil didiagnosis dengan COVID-19 diminta untuk menunda kunjungan ANC sampai mereka sembuh. Akibatnya pertumbuhan dan perkembangan janin tidak terpantau dengan baik (15).…”
Section: Pelayanan Anc Selama Pandemi Covid-19unclassified
“…Pregnant women faced difficulties in obtaining adequate antenatal care during the COVID-19 pandemic due to limited access to health care [ 14 , 15 ] and were reluctant to visit antenatal care due to fear of COVID-19 infection, resulting in a decrease in antenatal care visits [ 16 ]. Furthermore, pregnant women were concerned about their own and their babies’ health [ 17 ].…”
Section: Introductionmentioning
confidence: 99%